Effects of Aloe Vera Extract on Basal Cell Thickness and Lymphocyte Infiltration at the Gastroesophageal Junction in a Rat Model of Gastroesophageal Reflux Disease - Shella Violita; Tena Djuartina; Vetinly Vetinly; Iskandar Rahardjo Budianto (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Gastroesophageal reflux disease (GERD) is a chronic gastrointestinal disorder with increasing global prevalence. Aloe vera contains bioactive compounds with potential anti-inflammatory properties. This study aimed to evaluate the anti-inflammatory effects of Aloe vera extract in a Sprague-Dawley rat model of GERD.Methods: This experimental study included 32 male Sprague-Dawley rats randomly divided into eight groups: normal (N), negative control (NC), two positive controls receiving pantoprazole for 7 or 14 days (PCI and PCII), and four treatment groups receiving Aloe vera extract at doses of 250 or 500 mg/kg body weight for 7 or 14 days (DI–DIV). After treatment, the rats were euthanized and gastroesophageal junction (GEJ) tissues were collected for histopathological analysis. Basal cell thickness and lymphocyte infiltration were assessed. Data were analyzed using one-way ANOVA followed by post hoc testing.Results: Administration of Aloe vera extract at doses of 250 and 500 mg/kg body weight significantly reduced basal cell thickness compared with the untreated GERD group (p<0.05). However, no significant reduction in lymphocyte infiltration was observed (p>0.05).Conclusions: Aloe vera extract exhibits anti-inflammatory effects in GERD-induced rats by reducing basal cell thickness at the GEJ. These findings suggest its potential as a complementary therapeutic approach for GERD, although further studies are needed to evaluate long-term efficacy and safety.